A Phenomenological Exploration of AI's Impact in the Digital Communication Ecosystem - Yuniar, Nabila Alda; Bathesta, Yovi; Kamal, Kamal; Adhinugroho, Michael; Pertiwi, Setya Ambar; Harjanto, Rudy (PRoMEDIA, 2025)
Communication technology in the digital era has led to the expanding use of Artificial Intelligence (AI), which raises ethical concerns and possible benefits. This research examines the complex world of digital communication, focusing on ethics in the AI era. The central tension is between free expression and lowering the risks of spreading misinformation and deception. The idea is to establish ethical frameworks that maintain this hazardous balance. A phenomenological research technique is used to understand digital communication enthusiasts' lived experiences and viewpoints. Phenomenology gives a qualitative view of ethical challenges and possibilities, encapsulating the underlying character of AI-powered communication tool user interactions to examine the contradiction between free expression and hoax prevention to understand the formulation and usage of ethical norms for responsible communication in the AI era. The theoretical framework shows how AI affects digital communication practices. AI's ability to falsify information poses freedom of speech concerns, prompting an ethical assessment of these technologies. The study explores the potential and moral conundrums that arise from the nexus of communication, AI, and the digital world. It also discusses how the changing digital landscape affects communication ethics. It calls for the development of strong norms and processes to promote ethical digital communication practices, emphasizing the significance of ethical enforcement in its discussion. It explores the ways artificial intelligence (AI) may enrich the digital age by preventing misinformation while preserving freedom of speech. Proposing an enforcement ethic, the study aims to cultivate a digital ecosystem that prioritizes ethics and harnesses the transformative potential of AI.